Defect and maintenance on concrete in government building - Mohd Firdaos, Abdul Wahab (2012)
Malaysia is a developing country and many projects are being implemented. Some of the projects involve construction of buildings. Nevertheless, some of the buildings are poorly constructed and maintained. One of the components that need attention is concrete. The concrete structure need to be inspected and maintained regularly. Poor maintenance of concrete components will lead to the buildings being rendered not fit for occupancy. The main objectives of this study are to determine the types of concrete defect, the factors that cause concrete defects, the method of repairs and the problems faced by the Public Work Department (PWD) in carrying out the maintenance work. The study is carried out on government buildings in Terengganu. The data are collected through questionnaire and also from the records of the PWD. The data is analyzed by using average mean index. From the study, it was found that the main types of concrete defects are spalling and delamination. The factors that cause the defects are inefficient maintenance and poor construction method. The method of concrete repairs that are adapted by PWD are patching and sealing.